ANALYZING PT INDOSAT TBK’S PROFITABILITY BEFORE AND AFTER ACQUISITION - Lampah, Inggrit .; Tumbuan, Willem J.F.Alfa; Tumewu, Ferdinand . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Profitability is a crucial factor in a company. Strategies are applied to achieve the main goal of a company which is to gain more profit and one of them is to expand. PT. Indosat Tbk is implementing acquisition as a form of expanding their company and in performing the strategy, two possibilities might occur whether the company will success or a failure.This research used comparative and paired sample t-test analysis. To analyze the profitability, this research used 4 indicators, which are Return on Asset, Return on Equity, Net Profit Margin, and Gross Profit Margin. The data were taken in the form of annual report from year 2003 to 2013 official website of PT. Indosat Tbk and Indonesia Stock Exchange.Current research regarding with the profitability before and after acquisition issues of PT. Indosat Tbk showed a negative result that declared a new different strategy to gain more profit should be implemented. Based on this research, the negative result of the acquisition of PT. Indosat Tbk by Qtel caused by the increasing of assets and revenues are not in line with the profitability.Keywords: Profitability, Acquisition, Financial Ratio, Return on Assets, Return on Equity, Net Profit Margin, Gross Profit Margin